2004
DOI: 10.1080/10915810490471352
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of the Antimalarial Drug, AQ-13, in Rats and Cynomolgus Macaques

Abstract: The purpose of this study was to evaluate the bioavailability and pharmacokinetics of a new antimalarial drug, AQ-13, a structural analog of chloroquine (CQ) that is active against CQ-resistant Plasmodium species, in rats and cynomolgus macaques. Sprague-Dawley rats (n = 4/sex) were administered a single dose of AQ-13 intravenously (i.v.) (10 mg/kg) or orally (20 or 102 mg/kg). Blood and plasma samples were collected at several timepoints. AQ-13 achieved C(max) after oral administration at approximately 3 to 4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0
2

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 17 publications
3
15
0
2
Order By: Relevance
“…Second, they demonstrate that AQ-13, an AQ analogous to CQ, has similar linear pharmacokinetics in human volunteers, despite the fact that it requires a larger dose to achieve equivalent drug exposure because of a more rapid clearance. These results are also consistent with the preclinical studies, which suggested that the AEs of AQ-13 and CQ would be similar and that a dose adjustment would be necessary for AQ-13 because of its more rapid clearance [17,18]. Because this Phase I study has demonstrated the safety of AQ-13 doses up to 1,750 mg, the next logical study (after examining the effects of a fatty meal on the absorption of AQ-13) is a dose-finding efficacy (Phase 2) study in humans with uncomplicated P.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Second, they demonstrate that AQ-13, an AQ analogous to CQ, has similar linear pharmacokinetics in human volunteers, despite the fact that it requires a larger dose to achieve equivalent drug exposure because of a more rapid clearance. These results are also consistent with the preclinical studies, which suggested that the AEs of AQ-13 and CQ would be similar and that a dose adjustment would be necessary for AQ-13 because of its more rapid clearance [17,18]. Because this Phase I study has demonstrated the safety of AQ-13 doses up to 1,750 mg, the next logical study (after examining the effects of a fatty meal on the absorption of AQ-13) is a dose-finding efficacy (Phase 2) study in humans with uncomplicated P.…”
Section: Discussionsupporting
confidence: 87%
“…Because AQ-13 was cleared more rapidly than CQ in the preclinical studies [17,18], the protocol for the Phase I human studies included a dose adjustment step after the 600 mg dose (Figure 1). Because the information available about the effects of CQ on the QT interval was limited [28,29], these studies used Holter recordings to compare the effects of CQ and AQ-13 on the QT interval.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Preclinical studies have indicated increased efficacy of AQ-13 when compared to other derivatives [50]. Phase I first-in-human safety and efficacy studies have shown results similar to those observed with chloroquine.…”
Section: Aminoquinoline Scaffoldsmentioning
confidence: 98%
“…Progress in chemotherapy has been made using protease inhibitors to starve the parasites [5,6], using antimalarial acridones [7] and new 4-aminoquinolines [8] to counteract resistance, and using some modified chloroquine analogs [9]. Trioxanes derived from artemisinin (1), such as artemether ( 2c ) and sodium artesunate ( 2d ), are now being used clinically to cure malaria-infected people [10,11,12,13,14,15,16].…”
Section: Introductionmentioning
confidence: 99%